ANALISIS PENATAAN PARKIR KAWASAN PERKANTORAN PEMERINTAH KOTA PALEMBANG DI RUAS JALAN MERDEKA - Muhammad Rusedky; Farlin Rosyad; Wanda Yudha Prawira; Ely Mulyati (Ensiklopedia of Journal, 2025)
The increasing population and vehicle ownership in Palembang City, particularly in the Government Office area along Jalan Merdeka, have caused significant parking shortages. This situation forces many vehicles, both from employees and visitors, to use on-street parking, which disrupts traffic flow. This study aims to analyze parking characteristics, including volume, accumulation, duration, turnover rate, parking index, current parking demand, and projections for the next five years, as well as to identify effective parking arrangement alternatives. The research method involved a five-day field survey on weekdays at three main locations, measuring existing parking capacity, recording vehicle entries and exits, and analyzing parking characteristics based on the Technical Guidelines for Parking Facility Management (Directorate General of Land Transportation, 1996). The results indicate that the existing parking capacity does not meet the standard Space Unit for Parking (SRP), with an average parking index exceeding 100% for both two-wheeled and four-wheeled vehicles. This condition highlights the urgent need for additional or optimized parking spaces. Recommended solutions include developing centralized parking facilities, implementing multi-story or mechanical parking systems, and applying scheduled parking management to improve efficiency and reduce congestion. Keywords : Parking, Capacity, Parking Index, On-Street Parking